Who is afraid of “light”? - Kim, Mintai; Kang, Youngeun; Abu Bakar, Shamsul (Herbert Wichmann Verlag, 2013)
This study investigates the effects of outdoor lighting on people’s perceptions of nighttime landscapes. More specifically, it examines the relationship between lighting and specific physical features of nighttime landscapes in participants’ reports of fear. To accomplish this, a combination of eye-tracking and self-reported data were collected. This study ultimately presents design guidelines intended to reduce fear levels experienced in the nighttime landscape.